India’s China Policy on Conflict Management under Prime Minister Narendra Modi from Liberalism Perspective - Hue, Quach Thi; Oanh, Nguyen Thi; Hiep, Tran Xuan (Dirasat: Human and Social Sciences, 2025)
Objectives: This study aims to analyze India's border dispute management policy towards China under Prime Minister N. Modi. Despite differences, both India and China wish to maintain a stable relationship for cooperation due to development needs and the trend of increasing interdependence. Liberalism theory suitably explains India's policy, as states can cooperate based on common interests rather than complete harmony. Method: The paper employs a qualitative analysis method to examine India's conflict management policy regarding the China-India border issue under PM Modi (2014-2020). The findings indicate India adopts a pragmatic policy aimed at controlling and managing conflicts with Beijing over boundary questions. Results: This article initially studies India's conflict management policy towards China based on liberalism theory. Accordingly, while India previously took harsh countermeasures, the country now maintains an assertive policy to defend territorial sovereignty while pursuing conflict management with Beijing to prevent escalation into all-out war. Conclusion: The study suggests India's policy shift stems from economic interdependence and the trend of international cooperation, demonstrating India's strategic thinking influenced by factors like historical context, strategic culture, ideology, politics, and Modi's worldview building on predecessors. The findings conclude that competition in the border region causes “mistrust” in the India-China relationship. However, interdependence from globalization necessitates a peaceful, stable environment for India's economic development, prompting Modi to implement a policy of cooperation and competition with China. Although striving for peace and stable development, India will never compromise on territory or borders with China.